Pengaruh Kepemimpinan Instruksional Kepala Sekolah Terhadap Kinerja Mengajar Guru SMK Se-Kecamatan Bojongloa Kidul Kota Bandung - Shandy Nugraha Hidayat; Endang Herawan; Eka Prihatin (Universitas Pendidikan Indonesia, 2019)
Research is called “The Influence of Principal Instructional Leadership to the Teaching Performance of Vocational Secondary School Teacher at Bojongloa Kidul Bandung City.”This research using two variable, x variable is Principal Instructional Leadership and y variable is Teaching Performance. The study is done in 6 Vocational Secondary schools at Bojongloa Kidul Bandung with respondents research the school teacher in each school. In general the purpose of this research was to give how much influence of Principal Instructional Leadership to the Teaching Performance of Vocational Secondary School Teacher at Bojongloa Kidul Bandung City. The study is done by using the method descriptive and approach quantitative supported to the study literature. Technique data collection using a questionnaire, who became population is a teacher of vocational secondary school at Bojongloa Kidul Bandung City with a sample of 70 respondents. Analysis thinks in this study use some help program Microsoft Excel 2007 and application spss 21.0 for windows. The calculation on Weight Means Score (WMS), shows that Principal Instructional Leadership Vocational Secondary School Teacher at Bojongloa Kidul Bandung City be in the very high with an average all the aspects 4,38. For the performance of teachers to teach are in the high with an average all the aspects 4,31. Based on the calculation t test obtained thitung = 20.58 ttabel = 1.668 means that there is a very significant influence between Instructional Leadership Principal Teacher Teaching Performance Against SMK Bojongloa District of Bandung Kidul, by calculating the coefficient of determination stating their influence between the variables of 84.64%.